Evaluation of the Effect of a Single Intra-articular Injection of Allogeneic Neonatal Mesenchymal Stromal Cells Compared to Oral Non-Steroidal Anti-inflammatory Treatment on the Postoperative Musculoskeletal Status and Gait of Dogs over a 6-Month Period after Tibial Plateau Leveling Osteotomy: A Pilot Study - Taroni, Mathieu; Cabon, Quentin; Fèbre, Marine; Cachon, Thibaut; Saulnier, Nathalie; Carozzo, Claude; Maddens, Stéphane; Labadie, Fabrice; Robert, Clément; Viguier, Eric (Frontiers in Veterinary Science, 2017)
Objective: Compare the clinical and pressure walkway gait evolution of dogs after a Tibial Plateau Leveling Osteotomy (TPLO) for a Cranial Cruciate Ligament Rupture (CrCLR) and treatment with either a 1-month course of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) or a single postoperative intra-articular injection of allogeneic neonatal Mesenchymal Stromal Cells (MSCs). Study design: Prospective, double-blinded, randomized, controlled, monocentric clinical study. Animals: Sixteen client-owned dogs. Materials and methods: Dogs with unilateral CrCLR confirmed by arthroscopy were included. Allogeneic neonatal canine MSCs were obtained from fetal adnexa retrieved after C-section performed on healthy pregnant bitches. The dogs were randomly allocated to either the "MSCs group”, receiving an intra-articular injection of MSCs after TPLO, followed by placebo for 1 month, or the "NSAID group”, receiving intra-articular equivalent volume of MSCs-vehicle after TPLO, followed by oral NSAID for 1 month. One of the 3 blinded evaluators assessed the dogs in each group before and after surgery (1, 3 and 6 months). Clinical score, gait and bone healing process were assessed. The data were statistically compared between the 2 groups for pre- and postoperative evaluations. Results: Fourteen dogs (9 in the MSCs group, 5 in the NSAIDs group) completed the present study. No significant difference was observed between the groups preoperatively. No local or systemic adverse effect was observed after MSCs injection at any time point considered. At 1 month after surgery, bone healing scores were significantly higher in the MSCs group. At 1, 3 and 6 months after surgery, no significant difference was observed between the 2 groups for clinical scores and gait evaluation. Conclusion: A single intra-articular injection of allogeneic neonatal MSCs could be a safe and valuable postoperative alternative to NSAIDs for dogs requiring TPLO surgery, particularly for dogs intolerant to this class of drugs.